Mulheres artistas: narrativas, poéticas, subversões e protestos do feminino na arte contemporânea paraense - ASSIS, Sissa Aneleh Batista de (Universidade Federal do Pará, 2017)
This paper analyzes the works of women artists and contemporary plastic and visual art of Pará. However, I quote this search to Antonieta Santos Feio modernist painter to represent the woman of Pará. First, is presented starting from a historical representation of women from the statues of Venus Steatopygous of prehistoric sculptures of Venus from the Classical Era to contemporary reinterpretations. This work also traces the path of struggles and achievements for the professionalization of women in the arts to contemporary times. Later, a brief introduction to different perspectives on concepts of gender, identity, identification and social movements in contemporary releases that contributed to social, sexual and intellectual to the artistic universe. Research shows the female universe in the arts, women's artistic expression, the interpretation of the female artist about on women and the symbolic representation of the regional women. The artists chosen for this study are composed narratives, aesthetics and poetics of the feminine in contemporary art of Pará.